Tornadoes - Armbruster, Ann.; Taylor, Elizabeth A. (New York : F. Watts, 1989)
Describes the causes, different parts, and movements of tornadoes, discusses how they are tracked and studied by scientists, and suggests science projects and related activities.
Includes index.
Bibliography: p. 62.
Booklist.
Library Talk.
6.8
5-8
Keywords: Tornadoes -- Juvenile literature; Tornadoes; Tornadoes; Tornadoes